Formación en educación ambiental a docentes de ciclo básico de la Institución Educativa Distrital Altamira Sur Oriental Sede C - Ortiz Grijalba, María Elena (Universidad Antonio Nariño, 2023)
This document describes the research proposal focused on the training of basic cycle teachers, specifically from cycles I and III, of the Altamira Sur Oriental District Educational Institution, Headquarters C afternoon session in Environmental Education, through the design, implementation and evaluation of a didactic proposal that in the context of this research we have called a module.